1991
DOI: 10.1056/nejm199102213240801
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Interferon Gamma to Prevent Infection in Chronic Granulomatous Disease

Abstract: For patients with chronic granulomatous disease, interferon gamma therapy is an effective and well-tolerated treatment that reduces the frequency of serious infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(86 citation statements)
references
References 35 publications
0
85
0
1
Order By: Relevance
“…A multifaceted therapeutic approach has been responsible for the greatly improved prognosis in CGD. The key elements of the current therapy include the following: avoidance of certain sources of pathogens, use of prophylactic trimethoprim-sulfamethoxazole, early use of antifungal drugs, surgical drainage or debridement when feasible, granulocyte transfusions for poorly responding infections, and the use of prophylactic recombinant human interferon-γ [8, 10, 36, 37, 38]. Prophylactic antibiotics and interferon-γ have reduced bacterial infections, but there is also the danger of life-threatening fungal infections which are not altered by trimethoprim-sulfamethoxazole prophylaxis [36].…”
Section: Discussionmentioning
confidence: 99%
“…A multifaceted therapeutic approach has been responsible for the greatly improved prognosis in CGD. The key elements of the current therapy include the following: avoidance of certain sources of pathogens, use of prophylactic trimethoprim-sulfamethoxazole, early use of antifungal drugs, surgical drainage or debridement when feasible, granulocyte transfusions for poorly responding infections, and the use of prophylactic recombinant human interferon-γ [8, 10, 36, 37, 38]. Prophylactic antibiotics and interferon-γ have reduced bacterial infections, but there is also the danger of life-threatening fungal infections which are not altered by trimethoprim-sulfamethoxazole prophylaxis [36].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these in vitro data, and results from a small study that indicated restoration of the oxidative burst in 2 patients with CGD who received subcutaneous IFN-γ [41], a randomized double-blind placebo-controlled study was conducted in the early 1990s to determine the efficacy of IFN-γ in patients with CGD [43]. In that trial, 128 patients with CGD were randomly assigned to receive IFN-γ or placebo 3 times per week.…”
Section: Ifn-γmentioning
confidence: 99%
“…Although the administration of IFN-γ therapy was found to be effective in patients with either X-linked or AR CGD, the effect was more substantial in those with X-linked disease, particularly younger patients with X-linked CGD. In addition, IFN-γ was well tolerated in all populations, and the adverse-effect rate was minimal [43]. …”
Section: Ifn-γmentioning
confidence: 99%
“…Currently, infectious prophylaxis with trimethoprim-sulfamethoxazole and the aggressive treatment of acute infections has improved survival [23]. Subcutaneous injections of interferon-γ three times a week has greatly reduced the number of life-threatening infections for many patients [24]. Granulomas may respond to low-dose steroid therapy [25], but some require surgical resection.…”
Section: Clinical Manifestations and Current Therapymentioning
confidence: 99%